MERAIH LOYALITAS PELANGGAN - Mardalis, Ahmad (Universitas Muhammadiyah Surakarta, 2005)
Customer loyalty has been recognized as the dominant factor in a business organizations success.Therefore it has received considerable attention in both marketing and management theory and practice.This article describes factors that determine customer loyalty and explores the essential strategic considerations for companies contemplating the development of loyalty initiatives. It also establishescustomer satisfactions, service quality, institutionimage, and switching barrier are cultivated in a mannerthat leads to loyalty.